2019
DOI: 10.1177/0046958019850731
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Infections With Influenza and Noninfluenza Respiratory Viruses: Yemen, 2011-2016

Abstract: In 2010, Yemen started the surveillance for severe acute respiratory infections (SARIs) by establishing 2 sentinel sites in Sana’a and Aden city. This study aims to determine the proportions of influenza and noninfluenza viruses among SARI patients and to determine the severity of SARI and its associated factors. The data of SARI patients who were admitted to SARI surveillance sites at Al Johory hospital in Sana’a and Al Wahdah hospital in Aden city during the period 2011-2016 were analyzed. The proportions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
(32 reference statements)
3
10
1
Order By: Relevance
“…Overall, 83.2% (849/1021) of SARI patients were positive for > 1 respiratory viruses; human adenovirus was the predominant virus identified, at 22% (225/1021). HMPV was identified in 7.1% (72/1021) of SARI patients, consistent with other studies that identified HMPV in 6%–12% of SARI cases ( 12 , 13 ). The proportion of HMPV-positive patients with co-detected respiratory viruses was 63.9% (46/72).…”
Section: The Studysupporting
confidence: 90%
“…Overall, 83.2% (849/1021) of SARI patients were positive for > 1 respiratory viruses; human adenovirus was the predominant virus identified, at 22% (225/1021). HMPV was identified in 7.1% (72/1021) of SARI patients, consistent with other studies that identified HMPV in 6%–12% of SARI cases ( 12 , 13 ). The proportion of HMPV-positive patients with co-detected respiratory viruses was 63.9% (46/72).…”
Section: The Studysupporting
confidence: 90%
“…Influenza A/H1N1pdm09 and H3N2 were the most predominant subtypes throughout the study period, with influenza B primarily co‐circulating in the 2012‐2013 winter season. The subtypes we identified circulating over the 3 years are consistent with other population‐based surveillance studies in the MENA region and Northern Hemisphere 4,13‐15 . In a 6‐year sentinel surveillance study in Jordan of all ages, influenza A H3N2 predominately circulated in 2011‐2012 and H1N1pdm09 was more common in 2012‐2013 4 .…”
Section: Discussionsupporting
confidence: 86%
“…Search strategy used for the articles selected for the review based on the literature from PubMed and PubMed central using the key words given in Section 2 10‐68 …”
Section: Methodsmentioning
confidence: 99%